Analysis of interpersonal and emotional intelligence students in informatics learning in TJKT department at SMK Negeri 1 Sintang - Laurensius, Laurensius; Lisa, Yasinta; Setyawan, Antonius Edy Setyawan (PT The Collaboration UVW, 2023)
Interpersonal intelligence is intelligence in a person’s interactions with other people. Meanwhile, emotional intelligence is a person’s ability to control their emotions intelligently. This research aimed to evaluate students’ interpersonal and emotional intelligence in the Informatics subject majoring in TJKT at SMK Negeri 1 Sintang. This research used the mixed method, qualitative and quantitative descriptive forms, with teachers and 49 students as the subject. The object of this research was interpersonal intelligence and emotional intelligence. The data collection techniques used were observation techniques, direct and indirect communication techniques, and documentation. Meanwhile, data collection tools are observation sheets, interview sheets, questionnaires, and documentation. The research results showed that interpersonal intelligence: empathetic attitude 79%; prosocial attitude 80%; self-awareness 69%; understanding of social and ethical situations 81%; effective problem-solving skills 71%; communication effective 76%; and effective listening 79%. While emotional intelligence: self-awareness 79%; managing emotions 77%; empathetic attitude 78%; using emotions productively 79%; and building relationships 89%. So, it can be concluded that students’ interpersonal and emotional intelligence have a significant relationship with learning outcomes.